PENDAMPINGAN UMKM RUMAH BUMN SIDOARJO MELALUI LITERASI KEUANGAN SYARIAH DIGITAL - Hakim, Faris Kurnia; Syarofi, Muhammad; Putra, Allen Pranata; Lukiani, Eunike Rose Mita; Zakia, Arivia Fikratuz; Larasati, Fauziah; Sakapuspa, Brilliani Raras (LPPM STAI Muhammadiyah Probolinggo, 2025)
MSMEs contribute significantly to the national economy, but still face the challenge of low financial literacy, particularly sharia finance. This community service activity aims to improve MSMEs' understanding of digital sharia financial literacy, both regarding digital sharia financial products and the dangers of non-bank online loans and online gambling. Quantitative and qualitative methods were used in this MSME mentoring. In addition to distributing questionnaires using a linkert scale, educational interventions and interactive discussions were conducted to improve MSMEs' understanding of digital sharia financial literacy. The subjects who received mentoring were MSME business owners fostered by Rumah BUMN Sidoarjo. The results of this activity showed a significant increase in MSME understanding, reflected in four indicators after receiving mentoring. These indicators are knowledge of sharia financial products, interest in using sharia financial products, understanding the dangers of non-bank online loans, and understanding the dangers of online gambling. This activity proves that mentoring MSMEs through digital sharia financial literacy can improve MSME financial resilience in the digital era.